Technetium-99m-Human IgG Radiopharmaceuticals: Preparation, Biodistribution and Infection Imaging in Mice - WIDYASTUTI WIDJAKSANA; ANNA ROSELIANA; AGUS ARIYANTO; SRI AGUSWARINI; MARIALINA MARIALINA; GINA MONDRIDA (Fakultas Farmasi Universitas Pancasila, 2008)
Technetium-99m-Immunoglobulin-G preparation and analysis were carried out using human immunoglobulin-G (IgG) which was conjugated with hydrazinonicotinamide (HYNIC) prior to labeling with technetium-99m (99mTc), and the HYNIC-IgG molecules were stabilized with a co-ligand, tricine. Tricine was prepared both in the form of lyophilized kits and in frozen solutions and their stabilities were compared. The effect of pH on the labeling efhciency was also studied. Characterization of native IgG as well as the radiolabeled IgG were carried out using size exclusion HPLC, whereas the labeling efficiency of 99mTc-HYNIC-IgG was determined using thin layer and paper chromatographic methods. The stability of radiolabeled 99mTc-HYNIC-IgG at room temperature as well as in human serum were investigated by observing the radiochemical purity within 4 hours in vitro. The shelf-life of Lmlabeled HYNIC-IgG stored at -40°C and tricine kits stored at 4°C were determined. Biodistribution of 99mTc- HYNIC-IgG in healthy mice and in infection-induced mice and rats were also studied. The HPLC results showed that the native and radiolabeled IgG had similar retention times, which indicated that conjugation and radiolabeling processes did not affect the integrity of the IgG molecules. The radiochemical purity of 99mTc-HYNIC-IgG was high - more than 90% - without purification step, and the preparation was stable up to 4 hours. Tricine kits prepared at pH 3 was proven to produce clear solution and high labeling yield, while pH 4 produced slight opalescence solution which turned to turbid after a few hours. Biodistribution studies in healthy mice showed an obvious uptake in liver but normal distribution in other tissues, while biodistribution in infection-induced mice showed significantly different uptake between infected tissues, i.e higher than normal tissues. Blood clearance was achieved within 2 hours and excretion via urine and faeces were observed within 24 hours. It is concluded that the preparation using human IgG showed high uptake in the infection site, and the 99mTc-HYNIC-IgG can be a promising radiopharmaceutical for infection or inflammation imaging.